The Clinical Utility of Health‐related Quality of Life Assessment in Pediatric Cardiology Outpatient Practice. (12th September 2012) - Uzark, Karen; King, Eileen; Spicer, Robert; Beekman, Robert; Kimball, Thomas; Varni, James W.
Abstract Objectives Children with congenital heart disease may experience significant psychosocial morbidity related to impaired quality of life (QOL). The aim of this study was to evaluate the clinical utility of health‐related QOL assessment in a pediatric cardiology outpatient clinic. Design The Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Scales were completed by a convenience sample of 176 patients, aged 8–18 years, being seen in a pediatric cardiology clinic. Three cardiologists enrolled in this study reviewed the completed PedsQL during the clinic visit and recorded their responses to items reported to be a problem "Often" or "Almost Always." This utilization of the instrument was compared to standardized scoring and the practicality and perceived usefulness of the practice was evaluated by physician interview. Results PedsQL responses showed 38% of patients reporting significant (Often or Almost Always) problems on at least one domain (19% Physical Functioning, 18.2% Emotional Functioning, 11.4% Social Functioning, and 22.3% School Functioning problems). Using standardized scoring, the prevalence of scores below the cutoff score for clinically significant impaired QOL in each domain ranged from 10% to 20%, with agreement between scoring methods ranging from 89% to 93%, sensitivity 68% to 86%, and specificity 89% to 97%. Cardiologists reported interventions in 30.1% of patients. They found that the PedsQL was easy to use, did not interfere with clinic operations, required minimal time (1–5 minutes), and provided information that had an important impact on their practice in some patients. Conclusions This study demonstrates the clinical utility of health‐related QOL assessment using the PedsQL in a pediatric cardiology outpatient setting. Identification of significant impairments in QOL can impact clinical decision making and may change psychosocial outcomes in children with congenital heart disease.